A study on improving students’ reading comprehension using the Numbered Heads Together Technique - Rosnani Sahardin; Mukarramah Mukarramah; Anwar Hanafiah (Studies in English Language and Education, 2015)
This study deals with improving the reading comprehension of junior high school students through the Numbered Heads Together (NHT) technique. The objective is to find out if cooperative learning using NHT can improve the reading comprehension of the students. The data for this research was obtained from a field study using an experimental research design at a middle school in Aceh Besar with a one group time series design. From the study, it was found that the students’ mean scores from the pre-test and the post-test were different. The mean score of the students’ post-test was higher than the pre-test scores. To find out if the two mean scores were significantly different, they were tested using the t-test statistical procedure.  The result showed that they were significantly different (df = 8, alpha 0.05, t-table 17.550 2.0452). This indicated that Ha was accepted and Ho was rejected as hypothesized. Thus, cooperative learning using the NHT technique can improve the reading comprehension skills of middle school students.